2020
DOI: 10.3389/fnins.2020.00146
|View full text |Cite
|
Sign up to set email alerts
|

Altered Large-Scale Brain Functional Connectivity in Ocular Hypertension

Abstract: We hypothesized that assessment of brain connectivity may shed light on the underpinnings of ocular hypertension (OHT), characterized by raised intraocular pressure (IOP) and no typical glaucomatous findings. OHT carries a risk for future glaucoma development, thus representing a model of presymptomatic condition. In previous studies on glaucoma, we showed altered brain connectivity since the early stage and in case of normal IOP. In this pilot study, we used a multimodal MRI approach by modeling voxelwise mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The increase in the fALFF value of LP represents the activation of this brain area to adapt to visual changes. The role of maintaining normal visual function, and when OH progresses to glaucoma, such as POAG, the role of this activation adaptive mechanism is hindered, so that is why the fALFF value of the cuneiform lobe in glaucoma patients is significantly reduced, which perfectly meet the current view that ocular hypertension is regarded as a pre-glaucoma state ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The increase in the fALFF value of LP represents the activation of this brain area to adapt to visual changes. The role of maintaining normal visual function, and when OH progresses to glaucoma, such as POAG, the role of this activation adaptive mechanism is hindered, so that is why the fALFF value of the cuneiform lobe in glaucoma patients is significantly reduced, which perfectly meet the current view that ocular hypertension is regarded as a pre-glaucoma state ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 62%
“…Generally, OH is considered to be a pre-glaucoma state ( 7 , 8 ). Worldwide, glaucoma is the most common cause of irreversible blindness, and it is anticipated that by 2040, 111.8 million of the global population will have this disease ( 9 ). Since IOP is positively correlated with the development of glaucoma an understanding of the pathogenesis of OH is important to guide strategies for the prevention and treatment of glaucoma, a significant public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these observations are in keeping with recent findings supporting the hypothesis that glaucoma could be considered to be a neurodegenerative disorder involving the central nervous system (CNS) [ 4 , 11 , 12 , 13 , 14 , 15 ]. In this context, several studies have highlighted changes in grey matter (GM) [ 16 , 17 ], functional connectivity [ 14 , 18 , 19 , 20 ], and white matter (WM) [ 14 , 15 , 20 , 21 ] in glaucoma patients as compared with controls. For example, Frezzotti et al [ 14 ] found higher axial diffusivity (AD) in the middle cerebellar peduncle, corticospinal tract (CST), anterior thalamic radiation (ATR), and superior longitudinal fascicle (SLF) in primary open angle glaucoma (POAG) patients relative to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Although the whole CNS alterations significantly correlated with the stage of glaucoma and disease's severity , many studies highlighted how gray and white matter extensive changes may be detected already at early stages of glaucomatous disease (Yu et al, 2013;Frezzotti et al, 2016;Kasi et al, 2019) thus supporting the hypothesis that the CNS involvement is not only a secondary phenomenon related with optic nerve damage, but it may represent the result of an active cascade of pathological mechanisms evolving independently from the optic nerve degeneration. Taking together all the above described visual and non-visual brain connectivity alterations, it may be assumed that glaucomatous patients may suffer from brain processing dysfunctions localized at different levels, including visual and visuomotor tasks, memory and emotion, working memory and attention, default mode network and other multimodal brain functions (Zhang et al, 2016;Wang et al, 2017;Nuzzi et al, 2018;Giorgio et al, 2020).…”
Section: Glaucoma As a Neurodegenerative Diseasementioning
confidence: 99%